Recent developments in corporate finance - Ritter, Jay R., 1954- (Cheltenham, UK ; Northampton, Mass. : Edward Elgar Publishing, 2005)
This two-volume set reprints 24 of the most influential articles on corporate finance published during the period 1996 - 2003. Five topics are covered: capital structure, securities issuance, payout policy, corporate governance and diversification and internal capital markets.
Includes bibliographical references and index.
oif 26/03/15
Loan
Keywords: Corporations -- Finance; Corporate governance